IMPROVING STUDENTS’ ENGLISH PRONUNCIATION THROUGH LISTENING TO ENGLISH SONGS AT THE SECOND GRADE STUDENTS OF SMP SWASTA HARVARD MARTUBUNG - Rizky Sadilah; Reni Rosianna Lumban Gaol (Universitas Potensi Utama, 2021)
The objective of this study was to investigate whether listening to English songs significantly improve students’ English pronunciation by conducting Classroom Action Research (CAR). The subject of this research was the second grade of SMP Swasta Harvard Martubung which consisted of 30 students and was conducted in two cycles. The instrument of collecting data was quantitative data Sound Production Test (Test Produksi Suara) and qualitative data (observation sheet). Based on data analysis, the score of students’ Sound Production Test improved in every test. In the result of students’ tests were showed that the mean score of pre-test was 52,3. The mean score of post-test in Cycle I was 65,7. The mean score of post-test in Cycle II was 81,2. Based on observation sheet, it was found that teaching learning process ran well. After giving the treatment by listening to English songs, the students’ English Pronunciation in pronouncing English words improved. It was concluded that listening to English songs can improve the students’ English Pronunciation.